Media use and social capital among the youth: an analysis of civic engagement during leisure time = Korzystanie z mediów a kapitał społeczny wśród młodzieży: analiza aktywności obywatelskiej w czasie wolnym - Pavić, Željko; Livazović, Goran (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The decline in social capital, observed in recent decades, has become a major concern for researchers and policymakers. The main goal of this paper is to investigate to what extent media consumption by young people in their leisure time affects specific types of communal activities, defined as an element of social capital. The basic hypothesis that the authors aimed to test in this paper is that the consumption of entertainment-focused media content reduces community engagement while the consumption of informative and educational media content increases it.
Keywords: social capital; social media; youth; civic engagement; leisure time; kapitał społeczny; media społecznościowe; młodzież; zaangażowanie obywatelskie; czas wolny